Japanese rice straw community approaches in developing rice straw culture (case study : Inagaki Wara No Kai, Aomori Prefecture, Japan) / Pandu Purwandaru, Eka Permanasari and Akira Ueda - Purwandaru, Pandu; Permanasari, Eka; Ueda, Akira (Universiti Teknologi MARA, Perak, 2020)
The Japanese rice straw culture started from the Yayoi period, the start of wetland rice method of farming technique. The rice straw culture is spread across Japan, as the supply of the rice straw is high, and it does not require special tools to process it. The rice straw culture is performed both during the special events and everyday life. However, along with the modernization and industrialization of agriculture, the culture slowly disappears. It is increasingly difficult to find the rice straw culture in Japan. To prevent this, several rice straw communities create a movement to preserve the culture. Within their methods, the community focuses on pure preservation, preservation and development or pure development. An example of the community focusing on the preservation and development is the Inagaki Wara no Kai. With this method, this community help to preserve the traditional activities of Inagaki village while at the same time creating new events for wider community. The development is rooted in local and global issues and the process of preserving and developing the rice straw culture is documented through workshops, exhibition and festival. These activities are conducted in the cooperation with different stakeholders such as participants, research and development partners, facilitators, or sponsors.